Pengaruh Sistem Kepartaian Terhadap Penyelenggaraan Pemerintahan Daerah Dalam Mewujudkan Keadilan Sosial - Jumza, Muhammad Faiz Nail; Ulfah, Siti; Darmawansya Tenri Liweng, Andi (Qawanin Jurnal Ilmu Hukum, 2023)
The Influence of the Party System on the Implementation of The purpose of this research is to analyze and describe the influence of the party system on the implementation of local government in Pangkep Regency, South Sulawesi Province in realizing social justice and to analyze and describe the factors that influence political party support for the implementation of local government in Pangkep Regency, South Sulawesi Province in realizing social justice. Population is the whole subject under study. Departing from this understanding, it can be understood that the population is an individual or group or the whole subject to be studied in a study, including the community, and the Regional Government of Pangkep Regency. The sample is part of the population whose characteristics are to be studied. As for the number of samples to be taken, it consists of the community, (its members) and the social service. The results showed that the influence of the party system on the implementation of local government in Pangkep Regency, Sulawesi Province in realizing social justice, namely the ranks of the Regional House of Representatives. Based on their respective main tasks and functions consisting of various political parties for how to realize social justice and Internal Factors of the influence of political parties (parpol) the support of political parties (parpol) is derived from within the party itself, where political parties have a vision-mission for the welfare of the people, therefore political parties (parpol) strongly support the implementation of local government in realizing social justice in pangkep district. While external factors influence the support of political parties to the implementation of local government in Pangkep district in realizing social justice, namely support from the community and government figures so that political parties in Pangkep district fight for social justice by providing assistance to areas in need. Abstrak:Tujuan Penelitian ini adalah Menganalisis dan Mendeskripsikan Pengaruh Sistem Kepartaian Terhadap Penyelenggaraan Pemerintahan Daerah Kabupaten Pangkep provinsi Sulawesi selatan Dalam Mewujudkan Keadilan Sosial serta Menganalisis dan Mendeskripsikan Faktor-Faktor yang Mempengaruhi Dukungan Partai politik Terhadap Penyelenggaraan Pemerintahan Daerah Kabupaten Pangkep Provinsi Sulawesi Selatan Dalam Mewujudkan Keadilan Sosial. Populasi adalah keseluruhan subyek yang diteliti. Berangkat dari pengertian tersebut, dapatlah dipahami bahwa populasi merupakan individu-individu atau kelompok atau keseluruhan subyek yang akan diteliti dalam suatu penelitian, diantaranya masyarakat, dan Pemerintah Daerah Kabupaten Pangkep. Sampel adalah sebagian dari populasi yang karakteristiknya hendak diteliti. Sedangkan mengenai jumlah sampel yang akan diambil, terdiri atas masyarakat, (anggotanya) dan dinas sosial. Hasil penelitian menunjukkan bahwa Pengaruh sistem kepartaian terhadap penyelenggaraan pemerintahan daerah kabupaten pangkep provinsi Sulawesi dalam mewujudkan keadilan sosial yaitu para jajaran Dewan Perwakilan Rakyat Daerah berdasarkan tugas dan fungsi pokok masing-masing yang terdiri dari berbagai partai politik untuk bagaimana dapat mewujudkan keadilan sosial dan Faktor Internal pengaruh partai politik (parpol) dukungan partai politik (parpol) adalah berasal dari dalam partai itu sendiri, dimana partai politik mempunyai visi-misi untuk mensejahterahkan rakyat, maka dari itu partai politik (parpol) sangat mendukung penyelenggaraan pemerintah daerah dalam mewujudkan keadilan sosial di kabupaten pangkep. Sedangkan Faktor Eksternal pengaruh dukungan parpol terhadap penyelenggaraan pemerintahan daerah kabupaten pangkep dalam mewujudkan keadilan sosial yaitu dukungan dari masyarakat dan tokoh-tokoh pemerintah agar partai politik yang ada di kabupaten pangkep memperjuangkan keadilan sosial dengan memertahakan bantuan bagi daerah-daerah yang membutuhkan.